International Sanctions and Emigration - Jerg Gutmann; Pascal Langer; Matthias Neuenkirch (Center for Economic Studies and ifo Institute (CESifo), 2024)
In this first empirical analysis of how sanctions affect international migration, we apply two estimation strategies, a panel difference-in-differences model and an event study approach. Our dataset covers 79,791 dyad-year observations, reflecting migration flows from 157 origin countries to 32 (largely OECD) destination countries between 1961 and 2018. The data supports that UN and joint EU-US sanctions increase emigration from target countries by around 20 percent. Our event study results for joint EU-US sanctions imply a gradual increase in emigration over the course of a sanction episode. The impact of UN sanctions on international migration is smaller and less persistent. Moreover, the effects are driven by target countries with fewer political rights and civil liberties, where emigration substitutes for the costly voicing of dissent. Finally, our results do not support systematic gender differences in the effect of sanctions on migration.
Keywords: F22; F51; J16; O15; 330; exit; gender differences; international sanctions; migration; voice